Physical and Chemical Properties of Gelatin from Red Snapper Scales : Temperature Effects - Meliana Wahyuningtyas; Nurul Jadid; Perry Burhan; Lukman Atmaja (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2019)
The extent of applications in various fields makes the need for gelatin continue to increase in the global market. Fish gelatin is an alternative to mammalian gelatin and its use is more universal because it can be consumed by all religious followers. The high variability of fish gelatin properties is caused by the availability of many extraction methods to obtain it. This preliminary study was carried out to find the optimum range of gelatin extraction procedures using Red Snapper scales because it had not been widely studied, although it was reported that gelatin yield was not significantly different from the bone and skin part. The optimum condition of the extraction procedure was obtained by pre-treatment using 5 % CH3COOH with extraction temperature of 60 °C which produces 58.19% swelling of fish scales and yield of gelatin is 8.76% with the moisture quality of 6.68%, pH of 6.225, viscosity of 15.54 cP and the melting point of 60 °C. The functional groups of gelatin was also successfully confirmed by FT-IR spectra.